Income Inequality, the Psycho-social Environment and Health Comparisons of Wealthy Nations - John Lynch; George Davey Smith; Marianne Hillemeier; Mary Shaw; Trivellore Raghunathan; George Kaplan (Luxembourg Income Study (LIS), 2001)
Is the extent of income inequality associated with average population health differences between wealthy countries? And, are between-country variations in indicators of the psychosocial environment associated with between-country health differences? This study carries out the most complete international examination to date of associations between income inequality and low birth weight, life expectancy, self-rated health, and age- and cause-specific mortality among countries providing data in Wave III of the Luxembourg Income Study (LIS). The LIS is widely regarded as the premier study of income distribution in the world. The study also examines how aspects of the psycho-social environment such as distrust, belonging to organizations, volunteering (all proposed as measures of social capital) and perceived control over one's life circumstances were associated with between-country variations in health. Included is data on belonging to trade unions and the proportion of women elected to national government, as indicators of class relations within the labour market and broader socio-political participation of women.
Keywords: 330; Einkommensverteilung; Sozialstruktur; Sozialpsychologie; Gesundheit; Industrieländer